Case Report: Transcatheter Arterial Embolization for the Initial Management of Intra-Abdominal Hemorrhage From a Hepatic Tumor in a Cat - Kawamura, Yuta; Itou, Hiroki; Kida, Akitomo; Sunkawa, Hiroki; Kawamura, Kenji (Frontiers in Veterinary Science, 2021)
An 8-year-old Ragdoll cat was admitted to our hospital after its owner noticed sudden lethargy. Abdominal ultrasonography showed a large amount of blood in the abdominal cavity, and the cat was diagnosed as having hemorrhagic shock caused by the rupture of an intra-abdominal mass. Blood transfusion was performed on the 1st day of hospitalization. On the 2nd day, contrast-enhanced computed tomography (CT) was performed, and hemorrhage from a mass originating in the caudate lobe of the liver was noted. Transcatheter arterial embolization (TAE) was performed to stop the bleeding from the mass using Gelpart to embolize the feeding artery. The following day, fever and elevation of liver enzyme levels were observed, but these subsided within a few days. At discharge 5 days after TAE, no fluid was found in the peritoneal cavity, and no further intra-abdominal bleeding occurred. Sixty-six days after TAE, we were able to perform resection surgery with the cat in good condition. A partial response was observed on CT performed before surgery. Histopathology revealed cholangiocellular adenoma. The cat was doing well as of postoperative day 549. This case indicates that TAE may be effective for initial hemostasis and stabilization of conditions in animals with tumor-induced hemorrhage.